The effect of Phase II Cardiac Rehabilitation Frequency On Compliance for Regular Home-Based Exercise and Re-Hospitalization In Patients Post Coronary Artery Bypass Graft Surgery - DA Setyaningrum (ACI (Acta Cardiologia Indonesiana), 2017)
Background: Participation in a cardiac rehabilitation (CR) program can reduce the risk of death.....